Soil–Plant Nutrient Correlations of Mature Oil Palm on Peatlands - Putri Siregar, Hummaira Hasnaya (Sustainability Nexus: Journal of Agriculture, 2026)
Peat soils develop under prolonged water-saturated conditions and are typically characterized by very acidic pH, high organic carbon content, high cation exchange capacity, and limited availability of essential macronutrients, conditions that can constrain crop productivity. This study was conducted in Bintang Mas Village, Kubu Raya Regency, to examine the relationship between soil nutrient availability and leaf nutrient concentrations in oil palm stands aged 8 and 13 years, as well as to formulate appropriate fertilizer and liming recommendations. Soil and leaf samples were analyzed for key physical and chemical properties, and the data were evaluated using Pearson correlation analysis. The results indicated weak to moderate relationships between soil nutrients, leaf nutrient concentrations, and yield, none of which were statistically significant. Based on the observed nutrient status, fertilizer and liming applications were proposed to improve soil pH and nutrient availability, thereby supporting more sustainable oil palm production on peat soils.